Bilateral Avulsion Fracture of the Fibula Head of the Knee Associated with Avulsion Fracture of the Iliotibial Band: A Rare Case of Fracture Segond Associated with Arcuate Fracture - Jonatas Brito de Alencar Neto; Clodoaldo José Duarte de Souza; Márcio Bezerra Gadelha Lopes; Maria Luzete Costa Cavalcante; Luiz Holanda Pinto Neto (Case Reports in Orthopedics)
Fibular head avulsion fractures are rare and are so-called the arcuate signal. Avulsion fracture of the iliotibial band and anterolateral ligament is known as a Segond fracture, and it is another rare entity. We describe the case of a 27-year-old woman who was hit by a car and suffered polytrauma, mainly suffering injuries to both knees. Radiographs of the knees showed a Segond fracture associated with the arched signal bilaterally. The aim of this study is to present a rare case report and literature review of a bilateral fibular head avulsion fracture associated with an anterolateral tibial avulsion fracture.